Short-Term Axial Length Changes in Myopic Eyes Induced by Defocus Spectacles for Myopia Control - Rafael Iribarren; Abel Szeps; Carlos Kotlik; Liliana Laurencio; MartÍn De Tomas; Ricardo Impagliazzo; Gabriel Martin (Photonics, 2023)
Background. This study tested short-term axial length changes with Lenstar using a simple peripheral plus-add spectacle design. Methods. The subjects for this study were current users of monofocal glasses or contact lenses, aged 18–25 years, with myopic spherical refractions ranging from −1.00 to −5.00 diopters in both eyes. This study tested subjects while using a pair of special defocus spectacles that possess a central zone with the distance myopic correction and a peripheral zone with +3.50 added diopters. The procedure consisted of reading an online book with black letters on white background on a desktop computer, in two periods—one with the usual spectacles and the second with special defocus spectacles. Before and after these periods, 10 axial length measurements of the right eye were made with Lenstar and averaged up to three decimal points. Results. Seventeen subjects (thirteen female and four male; mean age 22.3 ± 5.5 years) participated in this study. The mean spherical equivalent of their right eye was −2.31 ± 1.06 diopters. There was a significant difference of +8.1 microns which increased the axial length from baseline when reading the usual prescription levels during the first 40 min period. When subjects read in the same situation with the defocus spectacles, the axial length significantly returned to baseline measurements, which were shortened by −10.6 microns. Conclusions. The decrease in axial length with these spectacles might indicate an effect on axial elongation signals from the choroid. These spectacles could be tested for myopia control purposes.